PERTIMBANGAN HAKIM DALAM MENYATAKAN GUGUR PERMOHONAN PRAPERADILAN (STUDI PUTUSAN NO. 1/PID.PRA/2019/PN.PNM) - Diah Ayu Sulistyaningrum; Moch Pring Musibatawi (Verstek, 2023)
This article analyzes the considerations judge's for dismissing the pre-trial in Court Decision Number 1/pid.pra/2019/Pn.Pnm. The purpose of this article is to determine whether the judge's considerations in declaring the pre-trial application for Court Decision Number 1/pid.pra/2019/Pn.Pnm in accordance with Article 82 paragraph (1) letter d of Criminal Law Procedure Code jo Decision of Constitutional Court Number 102/PUU-XIII/ 2015. This reseaarch is a normative reseacrh that is both prescriptive and applied. A case study approach was used in the research. Techniques for gathering data through library research. The legal sources used are primary and secondary legal materials. The results of the study showed that The judge's consideration for declaring the nullity of pre-trial application in Court Decision Number 1/pid.pra/2019/Pn.Pnm is accordane with Article 82 paragraph (1) letter d Criminal Procedure Code and Decision of Constitutional Court Number 102/PUU-XIII/2015, because the first trial was held regarding the subject matter.Keywords: Pretrial; Judge's Consideration; The Nullity of Pre-trial